Costa Rica : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Costa Rica. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation highlights that Costa Rican government recognizes the challenges and is planning a broad array of measures, although the political and social environment remains difficult. The Consultation focused on policies that would help restore fiscal sustainability, strengthen the inflation targeting framework, enhance resilience of the financial system, and boost potential and inclusive growth. The fiscal reform constitutes a critical step towards restoring fiscal sustainability, but full and timely implementation is key. Further frontloaded fiscal consolidation, based largely on revenue measures, should be implemented to further reduce debt and financing pressures, while taking measures to protect the poor. It is also recommended that monetary policy should continue to remain data dependent and balance downside risks to inflation stemming from slower activity and upside risks to inflation arising from tighter global financial conditions. Structural reforms, including those planned under the Organisation for Economic Co-operation and Development accession process should be implemented to improve competitiveness and foster inclusive growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet